TRADISI MENGHADIAHKAN PAHALA SURAT AL-FATIHAH KEPADA MAYIT - Alawiyah, Khofifah; Much Raf Rafy Al Ghiyats (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2023)
The reading of Surat Al-Fatihah for mayit is a tradition that is commonly carried out in the community regardless of differences of opinion regarding the delivery of merit to mayit. The results of this study mention that the tradition of reading Al-Fatihah is included as 'urf yang shahih. The difference of opinion conveyed the reading reward is caused by differences in scholars in using propositions that discuss a problem. But this difference should not create divisions between groups because a difference is a grace that must be addressed properly. This research uses a field research method with a deductive approach to see the phenomenon of the tradition of rewarding mayit, then condensed through related postulates. From this research, it was obtained that there were several differences in scholars regarding the delivery of merit to mayit or not. The difference is due to differences in the use of postulates. Some scholars consider that the hadith can be understood textually while others understand it contextually.